Prevalence of Helicobacter pylori Infection and its Relation with Body Mass Index in a Chinese Population. Issue 6 (25th September 2014) - Xu, Chengfu; Yan, Ming; Sun, Yan; Joo, Jungsoo; Wan, Xingyong; Yu, Chaohui; Wang, Qunyan; Shen, Chao; Chen, Peng; Li, Youming; Coleman, William G.
Abstract: Background: Helicobacter pylori infection is highly prevalent worldwide. The association between obesity and H. pylori infection is controversial in the literature. This study aims to investigate the prevalence of H. pylori infection and its relation with body mass index (BMI) in a Chinese population. Materials and methods: A cross‐sectional study was performed among adults who underwent health checkups at the First Affiliated Hospital, College of Medicine, Zhejiang University in 2013. The prevalence of H. pylori infection was examined by 13 C urea breath tests, and the association between prevalence of H. pylori infection and BMI was analyzed. Results: Of the 8820 participants enrolled, 3859 (43.8%) were positive for H. pylori infection. H. pylori ‐positive participants had a more unfavorable metabolic profile than H. pylori ‐negative participants. Overweight/obese participants showed a higher prevalence of H. pylori infection than that of lean participants, and a positive linear correlation between BMI and prevalence of H. pylori infection was observed. Both unadjusted and adjusted analysis revealed that BMI was significantly associated with risk factors of H. pylori infection. Conclusions: Our results showed that BMI was significantly and positively associated with H. pylori infection, and a high BMI was associated with an increased risk of the infection.